Mengubah Panas Buang Heater Mesin Injeksi Menjadi Energi Listrik dengan Peralatan Berbasis Termoelektrik - Agus Kurniawan; Alexander Satya Wiratama; Faris Abyan Adam; Hendsan Bhinar Prayoga; Taji Harya Prakosa (Universitas Muhammadiyah Yogyakarta, 2020)
This final project makes a device that produces electrical energy by utilizing waste heat from injection machines. The waste heat of the injection machine is converted into electrical energy using a thermoelectric. This device consists of an aluminum heatsink, aluminum plate, thermoelectric, MDF wood planks, engine gasket, and thermal paste. The heat generated by the injection machine is received by the hot side heatsink, then 4 units of the thermoelectric and the cold side heatsink. Thermoelectrics are arranged in series. The output from the thermoelectric is connected to a multimeter to test the amount of voltage and current generated. The number of thermoelectric-based equipment made of 2 (two) pieces and assembled in series. The test was carried out using an open circuit and a closed circuit with a load using a 1 watt LED lamp (Ω 55 Ω). The open circuit test results show that the largest voltage is generated at 10.80 volts with a hot side temperature of 108C and a cold side temperature of 64˚C. The results of the closed circuit test show that the greatest voltage produced is 2.64 volts with a hot side temperature of 108 C and a cold side temperature of 62 C. When thermoelectric based equipment is given a load, the voltage decreases because the voltage is divided into the given load. This equipment can be applied to turn on as many as 5 lamps with a power of 1 watt each which supports production activities in the injection workshop.